2003
DOI: 10.1046/j.1365-4362.2003.01743.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of histopathology in vitiligo

Abstract: Absence of melanocytes, increased number of Langerhans' cells, epidermal vacuolization, thickening of the basement membrane, T-cell inflammatory infiltrate, and neural alterations were noted in the vitiligo lesions. These results may explain the development of depigmentation, but do not yet fully explain why and how this occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 36 publications
(25 reference statements)
3
45
1
5
Order By: Relevance
“…Finally according to our data, we suggest an involvement of this dendritic subset in the pathogenesis of vitiligo. Previous studies [12,14,17] have demonstrated an increase of Langerhans cells in vitiligo skin without clearing the subset involved. We have already shown in another skin disease [16] the relevance of dendritic cells in the pathogenesis, defying their role consistent with the numerous subsets.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Finally according to our data, we suggest an involvement of this dendritic subset in the pathogenesis of vitiligo. Previous studies [12,14,17] have demonstrated an increase of Langerhans cells in vitiligo skin without clearing the subset involved. We have already shown in another skin disease [16] the relevance of dendritic cells in the pathogenesis, defying their role consistent with the numerous subsets.…”
Section: Discussionmentioning
confidence: 94%
“…As a lot of studies have provided contradictory results about the quantitative variation of Langerhans cells in the vitiligo-affected skin [12] and no previous data exist concerning the immunophenotypical distributions of specific markers of dendritic cells, we focused our attention on defining the ultrastructural features of lesional, perilesional, and non-lesional skin from vitiligo patients with a similar clinical history concerning the lesions' extension, duration of the disease, and absence of autoimmunity. We observed an increase of dendritic cells in lesional and perilesional vitiligo skin, with ultrastructural alterations in their mitochondria especially in perilesional skin [17].…”
Section: Introductionmentioning
confidence: 99%
“…Outras alterações também podem ser observadas, como dermatite de interface com infiltrado linfocitário na derme superficial (13) . Estas alterações são mais proeminentes no vitiligo ativo do que no estável (1,6) .…”
Section: Discussionunclassified
“…Alguns autores acreditam que melanócitos permaneçam no vitiligo, mas sem atividade melanogênica (4,10,15,19) , porém Montes et al (13) , por microscopia eletrônica, e Le Poole et al (6) , por imuno-histoquímica, demonstraram ausência de melanócitos nas áreas despigmentadas do vitiligo. Em nosso estudo, o caso 3 mostra na pele lesada células localizadas na camada basal da epiderme lembrando melanócitos, porém não imunomarcadas pelo HMB-45 (Figura 2B) nem pelo Melan-A; acreditamos que essas células correspondam a melanócitos, porém apoptóticos, e por isso não apresentam imunomarcação.…”
Section: Discussionunclassified
See 1 more Smart Citation